Supporting Sustainable Electricity Procurement within Manufacturing Companies : A multi-case study on management control systems and risk management - Ruhkala, Laura (My University, 2024)
Currently, the importance of sustainability within large manufacturing companies is heightened. The environmental part of sustainability includes becoming carbon neutral among other things. This is possible, for example, by purchasing guarantees of origin (GOs) for electricity in Europe. GOs prove that electricity is generated from specific energy sources, including renewable and nuclear energy. This research aims to study the management control systems and risk management that support the procurement of electricity generated from renewable and carbon dioxide-free nuclear energy with GOs. Such a study is essential as GOs are needed to minimise companies’ carbon dioxide emissions. Furthermore, GOs have a volatile market price. In 2022 and 2023, renewable GOs were multiple times the usual price level. Hence, focusing on the risk management processes is important when studying how to support sustainable electricity practices. The research approach adopted in this study includes a qualitative multi-case study. The data is collected with semi-structured interviews with representatives from manufacturing companies and sustainable electricity specialists with a broad understanding of GOs. In addition, secondary data from manufacturing companies’ websites, sustainability, and annual reports is utilised. The findings from this research provide evidence that GOs play an essential role in environmental sustainability. The management control systems that support sustainable electricity procurement can be divided into four systems as suggested in Simon’s (1995) levers of control framework: belief systems, boundary systems, diagnostic and interactive control systems. Belief systems represent the communication values, boundary systems include external and internal instructions, diagnostic control systems highlight the importance of energy efficiency, and interactive control systems, including meetings and life cycle analysis, focus on managing uncertainties. Regarding risk management, the most significant negative risk in GO markets is the price risk. This risk can be treated with hedging or diversification. Hedging can be done by purchasing GOs in advance or by making long-term contracts that include GOs. Diversification can be done by producing some of the energy, for example, with solar panels or by purchasing GOs in smaller portions at different times. In addition, the GO types are evaluated, as GOs from different sources have different prices.

Tällä hetkellä vastuullisuuden merkitys suurissa teollisuusyrityksissä on korostunut. Ympäristövastuullisuus pitää sisällään muun muassa hiilineutraaliuden tavoittelun, joka on mahdollista esimerkiksi hankkimalla sähkön alkuperätakuita. Alkuperätakuut osoittavat, että sähköä tuotetaan tietyistä energialähteistä kuten uusiutuvasta energiasta tai ydinenergiasta. Tutkielman tavoitteena on tutkia johdon ohjausjärjestelmiä ja riskienhallintaa, mitkä tukevat uusiutuvalla ja ydinenergialla tuotetun sähkön hankintaa alkuperätakuiden avulla. Tutkimus on tärkeä, sillä alkuperätakuita tarvitaan yritysten hiilidioksidipäästöjen minimoinnissa. Lisäksi alkuperätakuilla on vaihteleva markkinahinta. Esimerkiksi vuosina 2022 ja 2023 uusiutuvien alkuperätakuiden hinta oli moninkertainen tavanomaiseen hintatasoon verrattuna. Sen vuoksi riskienhallintaprosesseihin keskittyminen on tärkeää tutkittaessa tapoja tukea vastuullista sähkönhankintaa. Tämä tutkimus on toteutettu kvalitatiivisena monitapaustutkimuksena. Aineisto kerätään puolistrukturoiduilla haastatteluilla teollisuusyritysten edustajien ja vastuullisen sähkön asiantuntijoiden kanssa, joilla on laaja ymmärrys alkuperätakuista. Sen lisäksi hyödynnetään teollisuusyritysten verkkosivuja sekä vastuullisuus- ja vuosiraportteja. Tämän tutkielman tulokset osoittavat, että alkuperätakuilla on tärkeä rooli ympäristövastuullisuuden osoittamisessa. Vastuullisia sähkönhankintatapoja tukevat johdon ohjausjärjestelmät voidaan jakaa neljään ohjausvipuun Simonin (1995) Levers of Control – viitekehyksen mukaisesti. Nämä ohjausvivut pitävät sisällään uskomusjärjestelmät, rajoitejärjestelmät, diagnostiset ja interaktiiviset ohjausjärjestelmät. Uskomusjärjestelmät viestivät yrityksen arvoja, rajoitejärjestelmät sisältävät ulkoiset ja sisäiset ohjeet, diagnostiset ohjausjärjestelmät korostavat energiatehokkuuden merkitystä ja interaktiiviset ohjausjärjestelmät, mukaan lukien kokoukset ja elinkaarianalyysit, keskittyvät epävarmuuksien hallintaan. Riskienhallinnan kannalta merkittävin riski alkuperämarkkinoilla on hintariski. Tätä riskiä voidaan käsitellä hinnan suojauksella tai hajauttamisella. Suojaus voidaan tehdä ostamalla alkuperätakuita etukäteen tai tekemällä pitkäaikaisia sähkösopimuksia, jotka sisältävät alkuperätakuut. Hajauttaminen voidaan tehdä tuottamalla osa energiasta itse esimerkiksi aurinkopaneeleiden avulla tai ostamalla tarvittavat alkuperätakuut pienemmissä erissä eri ajankohtina. Sen lisäksi arvioidaan erityyppisiä alkuperätakuita, sillä alkuperätakuun energialähde vaikuttaa alkuperätakuun hintaan.
Keywords: Green electricity, Guarantee of Origin, Power Purchase Agreement, Management Control Systems, Risk Management, Vihreä sähkö, Alkuperäsertifikaatit, Pitkäaikaissähkösopimukset, Johdon ohjausjärjestelmät, Riskien hallinta